The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3847/1538-3881/aad4f6
|View full text |Cite
|
Sign up to set email alerts
|

UVIT Imaging of WLM: Demographics of Star-forming Regions in the Nearby Dwarf Irregular Galaxy

Abstract: We present a study of star forming regions and its demographics in the nearby dwarf irregular galaxy WLM using the Ultra-Violet Imaging Telescope (UVIT) multi band observations in three filters F148W, N245M and N263M. We find that the UV emission is extended at least up to 1.7 kpc, with the NUV emission more extended than the FUV. We create UV color maps ((F148W−N245M) and (F148W−N263M)) to study the temperature morphology of young stellar complexes with the help of theoretical models. We identify several comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…The profile of the SFR surface density also seems reliable, as it is similar to other estimates in the literature obtained from FUV emission (e.g. Mondal et al 2018). Our Σ SFR does not take into account the possible contribution of dustobscured star formation, which is instead included in Leroy et al (2008) profiles.…”
Section: The Vsf Law With Total Gassupporting
confidence: 86%
“…The profile of the SFR surface density also seems reliable, as it is similar to other estimates in the literature obtained from FUV emission (e.g. Mondal et al 2018). Our Σ SFR does not take into account the possible contribution of dustobscured star formation, which is instead included in Leroy et al (2008) profiles.…”
Section: The Vsf Law With Total Gassupporting
confidence: 86%
“…For example, the resultant decrease in central density and gas concentration may be extremely important for evolutionary changes of dwarf satel- lites, as demonstrated by Brooks & Zolotov (2014). Finding present day observational signatures which can trace the rapidity and strength of the potential fluctuations may provide further insight into the timescales, and mechanisms with which the DM core is growing, and can potentially differentiate feedback driven or particle scattering processes (e.g., gas and stellar spatial distributions; Mondal, Subramaniam & George 2018). This will be discussed in the subsequent section, however to first order the DM halo density profile we derive is in excellent agreement with the predictions from simulations which incorporate the effect of feedback driven halo expansion in a CDM framework.…”
Section: Dark Matter Density Profilementioning
confidence: 99%
“…Our analysis shows that the clumps detected in IC 2574 do not show any distinct mode in their orientation, whereas in WLM we noticed the majority of the clumps are aligned along south-west to north-east direction. Earlier studies by Kepley et al (2007); Mondal et al (2018) have shown the possibility of propagating star formation in the hook-like H I structure around the centre in WLM. The specific mode of orientation of the star-forming clumps may have a connection with this.…”
Section: Resultsmentioning
confidence: 91%
“…The clumps with bluer colour are seen between radii 0.4 -0.8 kpc. These clumps are mostly located in the regions R1, R2, and R3, as shown in Mondal et al (2018). The clumps identified in the central and the outer part of the galaxy are relatively redder in colour.…”
Section: Radial Distributionmentioning
confidence: 83%
See 1 more Smart Citation